Access, excess, and overdiagnosis: the case for thyroid cancer. (10th January 2014) - Hall, Stephen F.; Irish, Jonathan; Groome, Patti; Griffiths, Rebecca
Abstract The incidence of thyroid cancer in women is increasing at an epidemic rate. Numerous studies have proposed that the cause is increasing detection due to availability and use of medical diagnostic ultrasound. Our objective was to compare rates of diagnosis across different health‐care regions to rates of diagnostic tests and to features of both health and access of the regional populations. This is a population‐based retrospective ecological observational study of 12, 959 patients with thyroid cancer between January 1, 2000 and December 31, 2008 in Ontario Canada based on the health‐care utilization regions (Local Health Integration Networks) of the province of Ontario Canada. We found that some regions of Ontario had four times the rates of diagnosis of thyroid cancer compared to other regions. The regions with the highest use of discretionary medical tests (pelvic ultrasound, abdominal ultrasound, neck ultrasound, echocardiogram, resting electrocardiogram, cardiac nuclear perfusion tests, and bone scan), highest population density, and better education had the highest rates of thyroid cancer diagnoses. Differences in the rates of the ordering of discretionary diagnostic medical tests, such as diagnostic ultrasound, in different geographic regions of Ontario lead to differences in the rates of diagnosis of thyroid cancer.